The Effect of Macroeconomic Variables and The Russia-Ukrainian War on Exports in Indonesia - Heru Wahyudi (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
Indonesia is one of the countries that are active in international trade activities. This study examines the effect of macroeconomic variables consisting of natural resources rent, foreign direct investment, and government spending on Indonesian exports. In addition to macroeconomic variables, this study examines the effect of the Russia-Ukraine war on Indonesian exports. This study uses time series data from 1991-2021. The method used in this research is Ordinary Least Square (OLS). The results of this study show that natural resource rents have a positive effect on exports. In contrast, foreign direct investment, government spending, and the Russia-Ukraine war negatively and significantly impact Indonesian exports from 1991-2021. Simultaneously, natural resource rents, foreign direct investment, government spending, and the Russia-Ukraine war substantially affect Indonesian exports. This paper examines how macroeconomic factors, particularly the influence of the Russia-Ukraine war on exports, affect Indonesian exports, which are currently quite restricted. As a result, this study helps to understand the variables that influence exports in Indonesia.